Spatial variability in reproduction number and doubling time across two waves of the COVID-19 pandemic in South Korea, February to July, 2020 - Shim, Eunha; Tariq, Amna; Chowell, Gerardo (International journal of infectious diseases, 2021)
•South Korea has experienced two spatially heterogeneous waves of COVID-19.•Seoul and Gyeonggi Province experienced two waves of COVID-19 — in March and June 2020.•In densely populated Seoul and nearby areas, reproduction numbers exceeded 3.0.•The easing of social distancing measures resulted in the second wave. In South Korea, 13 745 cases of coronavirus disease (COVID-19) had been reported as of 19 July, 2020. To examine spatiotemporal changes in the transmission potential, we aimed to present regional estimates of the doubling time and reproduction number (Rt) for COVID-19 in the country. Daily series of confirmed COVID-19 cases in the most affected regions were extracted from publicly available sources. We employed established mathematical and statistical methods to investigate the time-varying reproduction numbers and doubling time for COVID-19 in Korea. At the regional level, Seoul and Gyeonggi Province experienced the first peak of COVID-19 in early March, followed by a second wave in early June, withRt exceeding 3.0 and mean doubling time ranging from 3.6 to 10.1 days. As of 19 July, 2020, Gyeongbuk Province and Daegu had yet to experience a second wave of the disease. During the first wave, mean Rt for these areas reached 3.5–4.4, and doubling time ranged from 2.8 to 4.6 days. Our findings support the effectiveness of control measures against COVID-19 in Korea. However, the easing of restrictions that had been imposed by the government in May 2020 facilitated a second wave in the greater Seoul area.